Managing organizational behavior - Tosi, Henry L.; Rizzo, John R.; Mero, Neal P. (Malden, Mass : Blackwell, 1999)
This book is about: Personality and individual differences; Attitudes, Perception and Judgment; Organizational accommodation; Theories of motivation; ...
Keywords: Economics; Business; Organization; Organizational behavior